Optimization of Bhabinkamtibmas in Reducing the Crime of Abuse on Children in the Jurisdiction of the Kuningan Polres - Laapen, Gian C. Jumario (Indonesian Journal of Police Studies, 2024)
The crime of molestation against children in the Kuningan police area every year increases from 2018-2019, the crime of molestation against children is one of the highest crime that occurred in the Kuningan police area where victims were children aged 13 years to 17 years who are still in junior high and high school . This study uses crime prevention theory, management, the concept of community development units, the concept of Community Policing, the concept of Guidance with Counseling, the concept Undang-undang Nomor 35 tahun 2014concerning child protection to analyze existing problems, with a qualitative approach. The focus of the research is the Optimization of Bhabinkamtibmas to prevent the crime of sexual abuse of children in the Kuningan police jurisdiction. Data collection techniques with interviews, observation and document review. This was done with the aim of wanting to know about the crime of sexual abuse of children in the Kuningan police area. The researcher found that the members of Bhabinkamtibmas had carried out their duties well but the implementation was not yet optimal due to several factors, internal factors that supported the collaboration between the Binmas Unit and Bhabinkamtibmas members, existing facilities and infrastructure, special allowances, factors limiting personnel limitations, facilities and infrastructure is still lacking while external factors that influence the community, religious leaders and community leaders for factors that inhibit community participation are still lacking, there is still a lot of unemployment and the distance of the residence of Bhabinkamtibmas to the target villages. Based on the findings, the authors recommend the need for networks as much as possible in order to prevent the crime of sexual abuse of children and the need for special material about the crime of sexual abuse of children.